Strategic collaboration of UMP, KPMKR transforms the education of Sabahan community - Sakinah, Abdullah (2022)
KOTA KINABALU, 26 January 2022 - Universiti Malaysia Pahang (UMP) and UMP Advanced are expanding strategic cooperation with the Ministry of Community Development and People’s Wellbeing of Sabah (KPMKR) including other agencies and departments Sabah to assist the transformation of technology-based community, especially the B40 group, single mothers, asnaf (zakat beneficiaries) and natives of the state.